Time and history in prehistory
1 online resource
Keywords: "Time and History in Prehistory explores the many processes through which time and history are conceptualised and constructed, challenging the perception of prehistoric societies as a-historical. Drawing equally on contemporary theory and illustrative case-studies and firmly rooted in material evidence, this book rearticulates concepts of time and history, questions the kind of narratives to be written about the past and underlines the fundamentally historical nature of prehistory. From a range of multi-disciplinary perspectives, the authors of this volume address the scales at which archaeological evidence and narrative are interwoven, from a single day to deep history and from a solitary pot to a complete city. In doing so, they argue the need for a multi-scalar approach to prehistoric data that allows for the interplay between short and long term, and for analytical units that encourage us to move continuously between scales. The growing interest in time and history in archaeology and across a wide range of disciplines concerned with human action and the human past highlights that these are exceptionally active fields. By juxtaposing varied viewpoints this volume bridges gaps in narrative, finds a place for inclusive histories and makes clear the benefit of integrative and inter-disciplinary approaches, including different disciplines and types of data"--